Foundations of SQL Server 2008 R2 business intelligence - Fouché, Guy 1961-; Langit, Lynn (The expert's voice in SQL server, 2011)
Foundations of SQL Server 2008 R2 Business Intelligence introduces the entire exciting gamut of business intelligence tools included with SQL Server 2008. Microsoft has designed SQL Server 2008 to be more than just a database. It’s a complete business intelligence (BI) platform. The database is at its core, and surrounding the core are tools for data mining, modeling, reporting, analyzing, charting, and integration with other enterprise-level software packages.